PENERAPAN HIDROPONIK RAMAH LINGKUNGAN DI KAMPUS SEBAGAI UPAYA URBAN FARMING BERKELANJUTAN - Ratnawati Yuni Suryandari; Ken Martina Kasikoen; Elsa Martini (LPSDI Bina Patria, 2025)
Hydroponic farming is a method of cultivating plants without soil, using alternative growing media, such as rockwool, combined with nutrient-rich solutions. This environmentally friendly method requires minimal land and can be implemented at low cost by utilizing recycled materials. In a campus setting, hydroponics has the potential to support environmental greening, enhance workplace comfort, and produce healthy, economically valuable crops. This approach aligns with the principles of sustainable development and the growing trend of urban farming in metropolitan areas. This community engagement program was conducted at the Center for Population and Policy Studies, Universitas Gadjah Mada (PSKK UGM), to enhance the knowledge and skills of the academic community in hydroponic agriculture. The program included awareness sessions, hands-on training, and mentoring in hydroponic gardening using a participatory approach. Beyond serving as an educational platform, the program aimed to promote healthy lifestyles, raise environmental awareness, and foster a balance between digital activities and interaction with nature. The results indicated increased interest and participation among campus residents in hydroponic practices. Participants reported feeling more comfortable in a greener campus environment and expressed enthusiasm to develop independent hydroponic gardens. This program is expected to serve as a practical model for implementing eco-friendly agriculture in higher education environments.